Pengaruh Lingkungan Kerja Fisik dan Lingkungan Kerja Non Fisik Terhadap Kepuasan Kerja Pegawai Pada Kantor Camat Belida Darat Kabupaten Muara Enim (Jurnal Manajemen dan Investasi (MANIVESTASI), 2023)
ABSTRACT This study aims to determine the analysis of financial incentives on the welfare of employees at the regional financial and asset management agency (BPKAD) in the province of South Sumatra. the method used in this study is a quantitative method with the number of samples studied were 95 employees. The data analysis technique used in this study is simple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and t test using the software program SPSS 22 for Windows. From the results of the t-test research that there is a significant effect between financial incentives (X) with a significant value of 0.000